Selective Oxidative Esterification from Two Different Alcohols via Photoredox Catalysis. Issue 1 (28th October 2016) - Yi, Hong; Hu, Xia; Bian, Changliang; Lei, Aiwen
Abstract: Esters functionalities are important building blocks that are extensively used in the chemical industry and academic laboratories. Direct oxidative esterification from easy‐available alcohols to esters would be a much more appealing approach, especially using O2 as terminal oxidant. Inputting external energy by photocatalysis for dioxygen activation, a mild and simple method for ester synthesis from two different alcohols has been achieved in this work. This reaction is performed under neutral conditions using O2 as the terminal oxidant. A variety of primary alcohols, especially long chain alcohols and secondary alcohols are tolerated in this system. Abstract : Photo for energy : Inputting energy by photocatalysis for dioxygen activation, a mild and simple method for ester synthesis from two different alcohols, is described. This reaction is performed under neutral conditions using O2 as the terminal oxidant. A variety of primary alcohols, especially long chain alcohols and secondary alcohols are tolerated in this system.